Enhancing Community Knowledge on Prudent Medication Use Based on Symptoms - Syilvi Rinda Sari; Hindri Syahputri; Kiki Rawitri; Cut Intan Annisa Puteri; Ferina Septiani Damanik; Muhammad Amin Nasution; Nia Novranda Pertiwi (Transformatif: Jurnal Pengabdian Masyarakat, 2026)
Irrational medication use remains a significant public health concern, often stemming from inadequate knowledge of symptom-based drug selection and self-medication practices. This community service activity aimed to enhance public knowledge on rational medication use, specifically focusing on drug classification, reading medication labels, and appropriate dosage instructions. Employing a community-based participatory approach, the activity was conducted at the UPT Puskesmas Teladan and involved 17 purposively selected visitors. The intervention, delivered through interactive lectures, two-way discussions, and medication label simulations supported by educational leaflets, was evaluated using pre-test and post-test instruments. The results demonstrated a notable improvement in participants' understanding, with average scores increasing from 4.94 (low category) to 7.94 (good category) on a 10-point scale. This improvement suggests that a targeted, interactive educational approach is feasible and holds promise for strengthening public knowledge on prudent medication use. This initiative highlights the potential for integrating similar community-based education programs into primary health services to promote safer self-medication behaviors.